PARTIAL BUDGETING ANALYSIS OF THE SEVENTY-FIVE PERCENT REDUCTION IN ACARICIDE USE AND ADOPTION OF INFECTION AND TREATMENT METHOD ON PASTORALISTS’ CATTLE IN NAROK COUNTY, KENYA. - Tenesi, Mukholi Gabriel (IJRDO - Journal of Business Management, 2023)
A 3-month prospective cross sectional and simulation study was carried out to determine partial budgeting analysis of infection and treatment method (ITM) using the Muguga cocktail vaccine with seventy-five percent in reduction in acaricide use on pastoralists cattle in Narok County, Kenya. The study was carried out in Osupuko and Loita sub-counties in Narok County. Partial budgeting analysis recorded positive net returns an indication of profitability of the ITM technology with seventy-five percent reduction in acaricide use. The ITM with seventy-five reductions in acaricide use realized a net return of Ksh.906.4 per immunized animal. This was significant because the information was generalized to the expansive Narok County. Thus, it can be concluded from the study that it is economically worthwhile to immunize cattle against ECF with seventy five reduction in acaricide use in the Narok County.